ENGLISH PHRASAL VERBS USED IN THE ALBUM “JUSTICE” BY JUSTIN BIEBER - Duha, Evi Merri Hartanti (Research on English Language Education, 2024)
The objective of this research was to find out the types and the meaning of phrasal verb in the album “Justice” by Justin Bieber. The researcher used qualitative method as metodology and descriptive qualitative as approach. In analyzing the data, the researcher used theory of Miles et al, therewere data condensation, data display, drawing and verifying conclusion. The source of the data was taken from the album “Justice” by Justin Bieber. Based on the results, there are two types of phrasal verbs that the researcher found, namely: transitive and intransitive phrasal verbs. Transitive phrasal verbs divided into two types are: Separable and Inseparable. There were 38 data of phrasal verbs, the most common phrasal verb were inseparable 22, separable 6, and intransitive 10. And also the researcher found the meaning semantically from phrasal verbs that contain in the album “Justice” by Justin Bieber. Based on the results of the analysis conducted by the researcher, the researcher concluded that there were a lot of phrasal verbs that contain the song lyrics of the album “Justice” by Justin Bieber and the use of phrasal verb in the album “Justice” by Justin Bieber is added the knowledge about the vocabulary of the phrasal verbs.